PENGEMBANGAN ATLAS PERSEBARAN SITUS SEJARAH DI DAERAH LAMPUNG SEBAGAI MEDIA PEMBELAJARAN SEJARAH - Chairul Anam; Bobi Hidayat (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
This study aims to develop atlas distribution of historical sites in the area of Lampung and describe its feasibility. The feasibility test is carried out at N 1 Kotagajah High School. Research uses research and development (R & D) methods. adapted from the Sugiyono Level 1 model (producing a design but not testing). The stages of research are potential problems, gathering information through observation, in-depth interviews, document collection, product design, media validation, media improvement, and completion of atlas distribution of historical sites in the area of Lampung products. The results of the study are the atlas distribution of historical sites in the area of Lampung learning media designed according to the 2013 curriculum KI and KD in the subject matter of the early lives of Indonesian people and the Indonesian nation's resistance strategy to European colonization. The results of validation by stage 1 media experts were 78% (Eligible) stage 2 of 95% (Very Eligible), stage 1 and stage 2 increased by 17%. The results of the validation by the material expert stage 1 were 75% (Eligible), stage 2 was 94% (Very Eligible), stage 1 and stage 2 increased by 18.7%. The results of student responses are 95% (Very Worthy). It was concluded that atlas distribution of historical sites in the area of Lampung deserves to be tested as a media for learning history.